Narcolepsy Quality-of-Life Instrument with 21 Questions: A Translation and Validation Study in Chinese Pediatric Narcoleptics - Li C (Dove Medical Press, 2021)
Chenyang Li,1 Liang Xie,2 Shaomei Shang,1 Xiaosong Dong,3 Xiaoling Wang,4 Long Zhao,3 Chi Zhang,3 Fang Han3 1Peking University School of Nursing, Beijing, People’s Republic of China; 2Department of Neurology, The Second Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of China; 3Sleep Medicine Center, Department of Respiratory and Critical Care Medicine, Peking University People’s Hospital, Beijing, People’s Republic of China; 4PKU-UPenn Sleep Center, Peking University International Hospital, Beijing, People’s Republic of ChinaCorrespondence: Fang HanSleep Medicine Center, Department of Respiratory and Critical Care Medicine, Peking University People’s Hospital, Beijing, 100044, People’s Republic of ChinaEmail hanfang1@hotmail.comObjective: This study aimed to translate and validate the narcolepsy quality-of-life instrument with 21 questions (NARQoL-21) in Chinese pediatrics with narcolepsy.Methods: NARQoL-21 was translated following the 10 steps of scale translation. The translated version was tested by exploratory factor analysis (EFA), confirmatory factor analysis (CFA), known-group validity, criterion validity, Cronbach’s α and test-rest reliability.Results: The Chinese version of NARQoL-21 consisted of two factors: (psychosocial factors and future outlook factor), including 20 items. EFA yielded 3 domains for psychosocial factors and 1 domain for future outlook factor. The Chinese version had a negative correlation with the overall Modified Epworth Sleepiness Scale (r = − 0.518, p< 0.001) and meaningful difference in score between drug naïve and treated group (p< 0.05). The Cronbach’s α coefficient was higher than 0.7 and intraclass correlation coefficient (ICC) ranged from 0.75 to 0.905, indicating that it had good reliability.Conclusion: The Chinese version of the NARQoL-21 is available and can be used to evaluate the health-related quality of life (HRQoL) of pediatric narcoleptics, despite that there is a shift in factors compared to the English version due to cultural differences. Future studies are recommended to further validate the scale in Chinese pediatrics with narcolepsy.Keywords: narcolepsy, pediatrics, quality of life, validation study